EFFICACY OF PRESYNCH-OVSYNCH-56 PROTOCOL IN INCREASING THE CONCEPTION RATE IN REPEAT BREEDER COWS - HEMALATHA, H; KANTHARAJ, S; MURUGAVEL, K; RAJU, M S; ANTOINE, D (The Indian Journal of Animal Reproduction, 2022)
A total of 30 repeat breeder cows that did not conceive even after three or more inseminations were divided into two equal groups. Cows in Group-I were kept as control and inseminated once during the observed estrus. Cows in Group-II (Treatment) were subjected to Presynch-Ovsynch-56 protocol and subjected to Fixed Time Artificial Insemination. Blood was collected from both the groups on the day of AI and day 6 post-AI for serum progesterone estimation. Cows in both groups that returned to estrus following the first AI were re-inseminated. There was no significant difference in the mean serum progesterone concentration between the groups both on the day of AI and day 6 post-AI. There was no significant difference in the first, second service and overall conception rate between the groups. However, Presynch-Ovsynch-56 protocol resulted in an acceptable overall conception rate of 33.33 % in repeat breeder cows compared to 20 % obtained in control repeat breeder cows.